TECHNIQUE FOR DETERMINING THE HEAT OF COMBUSTION IN THE PRODUCTION OF FUEL FROM SOLID MUNICIPAL WASTE WITH PREFERRED CHARACTERISTICS - Скляренко, Евгений; Воробйов, Леонід (SWorldJournal, 2023)
The issue of utilization of municipal solid waste (MSW) with the production of new types of fuel based on them is considered. The proposed technology for the production of fuel from solid waste with specified thermal characteristics, in particular, the h